An Overview of Collocations in Saeb Tabrizi's Sonnets - Mahla Arianpour; Maryam Alinezhad (Matn/Pizhūhī-i Adabī, 2023)
Collocations in literary texts, resulting from the poet and author's creativity in choosing proper words in the paradigmatic axis, along with the presentation of novel images, create a pleasant meaning and word proportionality that is sometimes considered the style of the poet or author. Thus, the study of collocations in literary texts is an interesting subject that provides a basis for a better understanding of the literary works and the style of their authors. In the present study, this linguistic phenomenon has been studied in Saeb Tabrizi's sonnets, a prominent poet with Indian style. The main objectives of this descriptive-analytical research are to show the most frequent types of collocations in Saeb's sonnets and their comparisons with today's Persian language collocations. To achieve these goals, the Safavi classification has been used. The research is corpus- based, and the necessary corpus was extracted from 50 Saeb sonnets (from 1400 to 1450) with about 573 verses.Findings indicate that although all kinds of collocations, except verb-verb, verb-adverb, and homonymy-homophony collocations, have been used in his sonnets, the meaning of associative collocations and their subtypes, such as hyponymy, is the most frequent. Results show that Saeb's collocation can be divided into three groups: 1: colloctions that apply with the same form and meaning in today's Persian language 2: collocations that are used in our utterances today with little change in form but with the same meaning; and 3: obsolete collocations that are not used today.Keywords: Collocations, Syntagmatic Collocation, Associative Collocation, Saeb's Sonnets. IntroductionCollocations in literary texts, resulting from the poet and author's creativity in choosing proper words in the paradigmatic axis, along with the presentation of novel images, create a pleasant meaning and word proportionality that is sometimes considered the style of that poet or author. In this way, collocation has a decisive role in rhetoric. Since this phenomenon is the result of specific lexical selection and also one of the methods for expressing meaning, knowing the best ways to use it, especially in literary works, leads to the formation of different styles. Therefore, by studying the collocations in literary works, it is possible to achieve different styles of expression in the pragmatic use of language elements. Thus, the study of collocationsin literary texts is an interesting subject that provides a basis for a better understanding of the literary works and the style of their authors. In the present study, this linguistic phenomenon has been studied in Saeb Tabrizi's sonnets, a prominent poet with Indian style.Research QuestionsIn this research, we try to answer the following questions:What are the most frequent types of collocations in Saeb's sonnets?Has Saeb used collocations to create new meanings and images?Are the collocations used in Saeb's poetry also used in the Persian language and contemporary poetry today?  Literature ReviewCollocations have been reviewed in the Persian language for the first time by Mohammad bin Omar Radovyani. He talks about symmetry and proportionality in his book titled “Tarjuman al-Balagheh”. After that, many scholars studied it. In the contemporary era, Jalal al-Din Homayi presented a new definition for collocations while explaining the opinions of past rhetoricians. According to Sirus Shamisa, collocation is achieved when some words are parts of a whole, and for this reason, there is proportionality and analogy between them. Safavi reviewed the history of collocations and classified collocations in the Persian language into three groups: modular, lexical, and associative collocations. Non-Persian linguists have also studied lexical relations and collocations. Firth (1957) was the first person who proposed the term collocations in his semantic theory and assumed it to be a semantic phenomenon, not a grammatical one. Sinclair (1966) refers to two types of collocations: accidental and meaningful collocations. According to Halliday and Hasan, repetition and collocation are important tools for lexical cohesion. Liones considers substitution and combination relations to be effective in collocations of words. MethodologyThe research was descriptive-analytical. The main goal was to show the most frequent types of collocations in Saeb's sonnets and their comparisons with today's Persian language collocations. In order to achieve these goals, the Safavi classification has been used as a theoretical framework. In his category, this phenomenon has been studied considering the syntactic, structural, phonetic, and semantic levels. The research is corpus-based, and the necessary corpus was extracted from 50 of Saeb's sonnets (from 1400 to 1450). which included about 573 verses. Extracted verses were placed in three categories: modular, lexical, and associative.     ConclusionStudying the related corpus revealed that all types of associative, lexical, and modular collocations were found in Saeb's sonnets, with a ratio of 65.1%, 31%, and 3.9%, respectively. In lexical collocations, noun-noun collocation had the highest frequency with 40.69%, and noun-adjective collocation is in second place with 39.53%. In terms of associative collocation, the semantic association with 40.88% had the highest frequency, and the structural association had the lowest frequency was 1.1%. Based on the analysis, it was determined that in Saeb's poetry, according to the classification of collocations as a theoretical framework, all types of collocations have been used, except for "verb-verb", "adverb-verb" and "homophone–homograph" collocations. Also, it was found that in Saeb's sonnets, collocations can be classified into three groups based on their function: 1- collocations that are used with the same word and meaning even today in contemporary language and poetry.2- collocative words that are used today with a slight change in wording but with the same meaning; 3- collocations in one of its words have been completely extinct and are not usedin today's language and poetry. Based on the findings, it can be concluded that Saeb has used collocation to create new meanings in his poems. In Saeb's sonnets, some of the words are placed in two or more types of collocations at the same time and overlap with each other.